המלאך, השמות, השירה: ולטר בנימין ופרדוקס המסורת - שחר, גלילי (מכאן, 2014)
The essay deals with the dialectic of tradition and its paradoxes - the paradoxes of revelation and delivery and the “demonic” aspects of the sacred, represented in Benjamin’s short autobiographic texts “Agesilaus Santander” of 1933. In his texts, Benjamin discusses these tensions regarding the figure of the angel, the (holy) names and the (liturgical) poem, re-interpreted from a modernist, “inverted” point of view as the work of a devil. It is the ambiguous, double structure of subjectivity, the demonic structure of desire and knowledge, that Benjamin is referring to himself (the German-Jewish author), opening also a radical view on the possibilities of the sacred in the “secular age”: being inverted, ironized, becoming ambiguous, yet maintaining a messianic power.